Feasibility of a Novel Mobile C-Reactive Protein-Testing Device Using Gold-Linked Electrochemical Immunoassay: Clinical Performance Study - Gondoh-Noda, Yuko; Kometani, Mitsuhiro; Nomura, Akihiro; Aono, Daisuke; Karashima, Shigehiro; Ushijima, Hiromi; Tamiya, Eiichi; Murayama, Toshinori; Yoneda, Takashi (JMIR Publications, 2020)
BackgroundHome-based care is one of the most promising solutions to provide sufficient medical care for several older patients in Japan. However, because of insufficient diagnostic devices, it is sometimes difficult to detect early signs of the occurrence or worsening of diseases, such as infections under home-based care settings. C-reactive protein (CRP) is highly sensitive to diagnosing infections, and its elevation can help diagnose acute infection in older patients. Therefore, a CRP-measuring device that can be used in such a specific occasion is needed for home-based care. However, aspects such as its size, weight, and procedure are still challenging with respect to the practical use of mobile devices that quantitatively measure CRP levels easily and quickly under home-based care settings. ObjectiveWe developed a new mobile, rapid CRP measurement device using a gold-linked electrochemical immunoassay (GLEIA) system. The aim of this study was to evaluate the feasibility of this mobile CRP-testing device. MethodsFirst, we assessed the performance of bare GLEIA-based electrode chips as the foundation of the device. After embedding the bare GLEIA-based electrode chips in a special plastic case and developing the mobile CRP-testing device, we further tested the device prototype using clinical blood samples. Finally, we evaluated the intra-assay variability for precision in the same condition and inter-assay variability for reproducibility in different conditions. ResultsBlood samples for analysis were obtained by direct vein puncture from outpatients (N=85; females: 57/85; males: 28/85; age: 19-88 years) at Kanazawa University Hospital in Japan. For performance evaluation of bare GLEIA-based electrode chips, we used 85 clinical blood samples. There was a significant positive correlation between the electrode-predicted CRP levels and the reference CRP concentrations (R2=0.947; P<.001). The assembled device was mobile (size 45×90×2.4 mm; weight 10 g) and disposable. The minimum volume of the sample needed for measuring CRP was 1.4 µL. The estimated preanalytical time was approximately 7 minutes and 40 seconds, and analysis time was approximately 1 minute and 10 seconds. Subsequently, for performance evaluation of the mobile CRP-testing device using GLEIA-based electrode chips, we used 26 clinical blood samples and found a significant positive correlation between the mobile device-predicted CRP levels and the reference CRP concentrations (R2=0.866, P<.001). The intra-assay variabilities were 34.2%, 40.8%, and 24.5% for low, medium, and high CRP concentrations, respectively. The inter-assay variabilities were 46.5%, 38.3%, and 64.1% for low, medium, and high CRP concentrations, respectively. ConclusionsOur findings suggest that this new mobile CRP-testing device might be suitable for use in home-based care settings.